The Process of \(e^+e^- → μ^+μ^-\) in the Randall - Sundrum Model, Supersymmetric Model and Unparticle Physics - Nguyen, Hau Thi; Dao, Thuy Thi Le (Communications in Physics, 2018)
The process of \(e^+e^- → μ^+μ^-\) in the Randall – Sundrum model, Supersymmetric model and Unparticle physics were studied in detail. The differential cross section and total cross section with different transmitted when polarized and non-polarized are compared and the numerical evaluation shows that they depend strongly on different transmitted.